Greece - Stein, R. Conrad (Chicago : Childrens Press, 1987)
Describes the geography, history, government, culture, and people of Greece.
Includes index.
Wilson's Junior High School.
7.0
5-8
5-9.
Keywords: Greece -- Juvenile literature; Greece; Greece